Letter (copy) : Spain - Citrine, Walter, 1887-1983
011-0117-001 WMC/WJB/AC/570 International 18th March, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, SPAIN. For your information, we give below copy of a telegram which reached us today from Valencia. We should like to receive an exact translation from you, in order to confirm our own interpretation. Yours faithfully, General Secretary. PRESIDENTE CONSEJO DE MINISTROS Y MINISTRO GUERRA A PRESIDENTE FEDERACION INTERNACIONAL TRADE UNIONS E INTERNACIONAL SOCIALISTA Y DEL TRABAJO LONDRES - EN NOMBRE DEL PUEBLO ESPAÑOL ANTIFASCISTA E EN EL DE SU GOBIERNO AGRADEZCO Y FRATERNALMENTE CORRESPONDO AL SALUDO RECIBIDO DE CONFERENCIA INTERNACIONAL AGRADECIENDO ASIMISMO OFRECIMIENTO REALIZAR CAMPANA FAVOR ESPANA REPUBLICANA - NOSOTROS POR NUESTRA PARTE REAFIRMAMOS ANTE EL MUNDO NUESTRA FIRME VOLUNTAD DE VENCER. 292/946/11/117